IFNβ Is a Potent Adjuvant for Cancer Vaccination Strategies - Audsley, Katherine M.; Wagner, Teagan; Ta, Clara; Newnes, Hannah V.; Buzzai, Anthony C.; Barnes, Samantha A.; Wylie, Ben; Armitage, Jesse; Kaisho, Tsuneyasu; Bosco, Anthony; McDonnell, Alison; Cruickshank, Mark; et al. (Frontiers in Immunology, 2021)
Cancer vaccination drives the generation of anti-tumor T cell immunity and can be enhanced by the inclusion of effective immune adjuvants such as type I interferons (IFNs). Whilst type I IFNs have been shown to promote cross-priming of T cells, the role of individual subtypes remains unclear. Here we systematically compared the capacity of distinct type I IFN subtypes to enhance T cell responses to a whole-cell vaccination strategy in a pre-clinical murine model. We show that vaccination in combination with IFNβ induces significantly greater expansion of tumor-specific CD8+ T cells than the other type I IFN subtypes tested. Optimal expansion was dependent on the presence of XCR1+ dendritic cells, CD4+ T cells, and CD40/CD40L signaling. Therapeutically, vaccination with IFNβ delayed tumor progression and synergized with anti-PD-L1 checkpoint blockade therapy (CPB) to promote overall survival. This work demonstrates the potent adjuvant activity of IFNβ, highlighting its potential to enhance cancer vaccination strategies alone and in combination with CPB.